Geomagnetic field disturbances produced by Sychuan earthquake on April 20th 2013 (Ms=7,0) - A. L. Sobisevich; E. A. Rogozhin; L. E. Sobisevich; K. H. Kanonidi; A.V. Kendzera; A. V. Marchenko; M. I. Orlyuk (Геофизический журнал, 2014)
Results of observations on location of wave disturbances registered during the preparation and development of the earthquake in the territory of China in Sychuan proovince on April 20th 2013 are analyzed. Experimental data have been obtained at the North Caucasian geophysical observatory, a part of Laboratory of Applied geophysics and volcanology of the IEPh RAS, situated in the area of the Elbrus volcanic center (North Caucasis) [Sobisevich, Gridnev et al., 2008] and the scientific stationary IZMIRAN (Karpogory, subauroral area) as well as magnetic observatories «Odessa» and «Kiev» in the territory of Ukraine. In the structure of observed abnormal magnetic disturbances in variations of the earth’s magnetic field, precursors of the earthquake, specific magnetic pseudo-wave forms of ULF range have been distinguished and partly analyzed, which reflect the processes of preparation and development of the crustal earthquake under examination. Materials on mac-roseismic and seismologic manifestations of the processes of preparation of the earthquake source as well as brief information on its tectonic location have been presented.